Adsorption of Phenol from Aqueous Solution Using Zn/Al Layered Double Hydroxides-Cellulose Composite - Risfidian Mohadi; Amri; Muhammad Badaruddin; Nur Ahmad; Aldes Lesbani (Science and Technology Indonesia, 2023)
The successful synthesis and preparation of Zn/Al layered double hydroxide, cellulose, and Zn/Al-cellulose materials were analyzed using XRD, FT-IR, and BET. The diffraction peaks of Zn/Al layered double hydroxide are at 10.3°; 20.3°; 34.8°; and 60.40°, while the diffraction peaks of cellulose are at 15.5°; 22.4°; and 34.5°. Diffraction peaks on Zn/Al layered double hydroxide and cellulose were observed at 3442 cm-1, 1642 cm-1, 1440-1620 cm-1, 1351 cm-1, 1153 cm-1, and 400-800 cm-1. The surface area of the material after the composite increased from 1.968 to 13.615 m2/g. The optimum pH for Zn/Al LDH was pH 4, pH 10 for cellulose, and pH 2 for Zn/Al-cellulose. The isotherm data of Zn/Al LDH and cellulose followed the Freundlich model, while Zn/Al-cellulose followed the Langmuir model. The reuse of adsorbents in the adsorption process can be used up to 3 times.